2018
DOI: 10.1016/j.jbiomech.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of knees with osteoarthritis show reduced lateral femoral roll-back and maintain an adducted position. A systematic review of research using medical imaging

Abstract: Differences in kinematics between osteoarthritic and healthy knees were observed, however, these differences were more subtle than expected. The synthesis and progress of this research could be facilitated by a consensus on reference systems for axes and kinematic reporting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This may be due to the fact that the contact point trajectories were measured during weight-bearing quasi-static squat while the contact forces are estimated during gait. Yet, a recent systematic review showed that the contact point trajectories obtained by biplane X-ray images during quasi-static squat matched the contact point trajectories obtained by fluoroscopy, MRI or CT during other activities (gait, step-up, kneeling, lunge) [5]. It is possible, in both healthy volunteers and OA patients, to measure the contact point trajectories during gait using bi-plane fluoroscopy [12], however, to the authors' knowledge, this information has never been introduced in subject-specific musculoskeletal model so far.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may be due to the fact that the contact point trajectories were measured during weight-bearing quasi-static squat while the contact forces are estimated during gait. Yet, a recent systematic review showed that the contact point trajectories obtained by biplane X-ray images during quasi-static squat matched the contact point trajectories obtained by fluoroscopy, MRI or CT during other activities (gait, step-up, kneeling, lunge) [5]. It is possible, in both healthy volunteers and OA patients, to measure the contact point trajectories during gait using bi-plane fluoroscopy [12], however, to the authors' knowledge, this information has never been introduced in subject-specific musculoskeletal model so far.…”
Section: Discussionmentioning
confidence: 98%
“…This was reported for subject-specific contact point trajectories of healthy volunteers which remain aligned with the medial and lateral plateau centrelines. In the pathologic case such as osteoarthritis (OA), the contact point trajectories appear to be shifted in the medial direction [4] and to demonstrate a lower excursion in the lateral compartment [5].…”
Section: Introductionmentioning
confidence: 99%
“…Differences between OA and healthy deep flexion kinematics have been supported in the literature. 13 Specifically, maximal flexion is commonly reported to be reduced in OA knees when compared to healthy. 12 In OA the soft tissues of the knee are affected in a number of ways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, flattening and reduced sphericity of the femoral condyles, have been reported to influence superior-inferior position throughout flexion 2,3,43 . Furthermore, a recent systematic review by Scarvell et al 13 reported OA knees to have reduced AP translations, maintain a more anterior position and have reduced axial rotations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation